ANALYSIS CONFLICT OF NORMS BETWEEN SEMA NUMBER 2 OF 2023 AND THE PRINCIPLES ON CIVIL REGISTRATION OF ADMINISTRATION LAW - Arina Nur Fazila; Zakaria Nuriman Wanda; Elviana Risqa Nur Fadila; Avany Mahmudah (Qaumiyyah: Jurnal Hukum Tata Negara, 2026)
Interfaith marriage has long been a social phenomenon within Indonesia’s multicultural society, yet it continues to present complex and ongoing legal and social challenges. The issuance of the Supreme Court Circular Letter (SEMA) Number 2 of 2023, which restricts the registration of interfaith marriages, has resulted in normative disharmony with the provisions of Law Number 23 of 2006 concerning civil registration. This study employed a normative juridical method with an analysis of legislation, legal doctrine, and judicial decisions to examine the normative disharmony between SEMA and the Civil registration Law, as well as its legal implications on the principles of legal certainty, human rights protection, and social justice. The findings revealed that the restrictions on interfaith marriage registration stipulated in SEMA potentially cause legal uncertainty, multiple interpretations in law enforcement, and violations of citizens’ constitutional rights to obtained valid and legally recognized civil documentation. Furthermore, such policy may exacerbate religion-based discrimination and limit interfaith couples’ access to essential legal protection and administrative services. In conclusion, regulatory harmonization between SEMA and the Civil registration Law is imperative to ensure legal certainty, safeguard human rights, and respect prevailing religious norms and social diversity within society. This study recommends revising SEMA and formulating inclusive policies as efforts to realize legal justice and constitutional rights protection for all citizens without discrimination. Abstrak Perkawinan beda agama telah lama menjadi fenomena sosial dalam masyarakat Indonesia yang multikultural, namun masih menimbulkan berbagai persoalan hukum dan sosial yang kompleks. Terbitnya Surat Edaran Mahkamah Agung (SEMA) Nomor 2 Tahun 2023 yang membatasi pencatatan perkawinan beda agama menimbulkan disharmoni normatif dengan ketentuan dalam Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan, doktrin hukum, dan putusan pengadilan untuk menganalisis disharmoni normatif antara SEMA dan Undang-Undang Administrasi Kependudukan serta implikasi hukumnya terhadap prinsip kepastian hukum, perlindungan hak asasi manusia, dan keadilan sosial. Hasil penelitian menunjukkan bahwa pembatasan pencatatan perkawinan beda agama sebagaimana diatur dalam SEMA berpotensi menimbulkan ketidakpastian hukum, perbedaan penafsiran dalam penegakan hukum, serta pelanggaran terhadap hak konstitusional warga negara untuk memperoleh dokumen administrasi kependudukan yang sah dan diakui secara hukum. Selain itu, kebijakan tersebut berpotensi memperkuat diskriminasi berbasis agama dan membatasi akses pasangan beda agama terhadap perlindungan hukum serta layanan administrasi yang esensial. Oleh karena itu, harmonisasi regulasi antara SEMA dan Undang-Undang Administrasi Kependudukan diperlukan untuk menjamin kepastian hukum, melindungi hak asasi manusia, serta menghormati norma keagamaan dan keberagaman sosial yang hidup dalam masyarakat. Penelitian ini merekomendasikan revisi terhadap SEMA dan perumusan kebijakan yang lebih inklusif sebagai upaya mewujudkan keadilan hukum dan perlindungan hak konstitusional bagi seluruh warga negara tanpa diskriminasi.